Growth of single-layer boron nitride dome-shaped nanostructures catalysed by iron clusters. Issue 32 (3rd August 2016) - Torre, A. La; Åhlgren, E. H.; Fay, M. W.; Ben Romdhane, F.; Skowron, S. T.; Parmenter, C.; Davies, A. J.; Jouhannaud, J.; Pourroy, G.; Khlobystov, A. N.; Brown, P. D.; Besley, E.; et al.
Abstract : We report on the growth and formation of single-layer boron nitride dome-shaped nanostructures on the step edges of hexagonal boron nitride flakes mediated by small iron clusters. Abstract : We report on the growth and formation of single-layer boron nitride dome-shaped nanostructures mediated by small iron clusters located on flakes of hexagonal boron nitride. The nanostructures were synthesized in situ at high temperature inside a transmission electron microscope while the e-beam was blanked. The formation process, typically originating at defective step-edges on the boron nitride support, was investigated using a combination of transmission electron microscopy, electron energy loss spectroscopy and computational modelling. Computational modelling showed that the domes exhibit a nanotube-like structure with flat circular caps and that their stability was comparable to that of a single boron nitride layer.